Perceived parenting style and self-esteem among adolescents of a secondary school - Maiya Malla, Sanu; Bajracharya, Shanti; Shrestha, Sarala (Journal of Chitwan Medical College, 2024)
Background: Parenting plays a significant role in the overall development of a child. Positive parenting techniques help the child to develop positive attitude, confident social behaviour and increase self-esteem. The main objective of this study was to find out the perceived parenting style and self-esteem among adolescents. Method: A descriptive cross-sectional study was conducted among 218 adolescents selected by using stratified proportionate random sampling technique from grade VII-XII of a secondary school. Self-administered questionnaire consisting of “Perceived Parenting Style Scale and Rosenberg Self-esteem Scale” was used to collect data. Data were entered in SPSS version 16 program and analysed using descriptive statistics i.e., frequency, percentage, mean and standard deviation and inferential statistics i.e. Karl Pearson correlation co-efficient, Chi–square test and Fischer’s exact test. Result: Out of 218 adolescent participants, 190(87.1%) perceived parenting style as authoritative, 20(9.2%) perceived authoritarian and 8(3.7%) perceived permissive parenting style. Majority 158(72.5%) of them had normal to high level of self-esteem. Authoritative parenting style was positively correlated (r=0.301, p=<0.001) with adolescents’ self-esteem, whereas authoritarian and permissive parenting style had negatively correlated (r=-0.377, p=<0.001 and r=-0.317, p=<0.001) respectively. There was significant association of parenting style with respondents’ ethnicity and religion.